2016
DOI: 10.1002/2015jc011443
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of the meridional overturning circulation in the South China Sea and its connection with inter‐ocean transport based on SODA2.2.4

Abstract: We have proposed a five‐layer‐scheme to investigate the volume transport through the South China Sea (SCS) based on the updated Simple Ocean Data Assimilation (SODA2.2.4) product. By demonstrating horizontal transport in each layer, we have revealed different formation mechanisms for the meridional overturning circulation (MOC) in winter and summer in the SCS. Our analysis suggests three meridional circulation systems in the SCS: (1) the seasonal monsoon‐driven circulation in the surface layer, i.e., southward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
(89 reference statements)
2
18
0
Order By: Relevance
“…The intermediate layer, defined by a potential density range of 26.40–27.62 kg m −3 , lies in an average depth range of 400–1850 m in the Luzon Strait. The mean volume flux is eastward in the Luzon Strait, which infers that the North Pacific Intermediate Water (NPIW, with characteristic density of 26.73 σθ) is impeded to intrude into the SCS [ Qu et al ., ; Li and Qu , ; Liu et al ., ; Zhu et al ., ]. In this density layer, water flows southward from the SCS to Sulu Sea through the Mindoro Strait, consistent with the bottom‐intensified deepwater overflow there based on satellite‐derived data [ Qu and Song , ].…”
Section: Data and Methods Of Analysissupporting
confidence: 80%
See 3 more Smart Citations
“…The intermediate layer, defined by a potential density range of 26.40–27.62 kg m −3 , lies in an average depth range of 400–1850 m in the Luzon Strait. The mean volume flux is eastward in the Luzon Strait, which infers that the North Pacific Intermediate Water (NPIW, with characteristic density of 26.73 σθ) is impeded to intrude into the SCS [ Qu et al ., ; Li and Qu , ; Liu et al ., ; Zhu et al ., ]. In this density layer, water flows southward from the SCS to Sulu Sea through the Mindoro Strait, consistent with the bottom‐intensified deepwater overflow there based on satellite‐derived data [ Qu and Song , ].…”
Section: Data and Methods Of Analysissupporting
confidence: 80%
“…The cyclonic and anticyclonic circulations are separated by the zero stream‐function contour line associated with the zero zonally integrated wind stress curl line or the separating point of the western boundary current to the east of Vietnam [ Gan and Qu , ]. Furthermore, the wind driven current flows inward to the SCS in winter but outward to the western Pacific Ocean in summer in the Luzon Strait above the isopycnal surface 24.2 σθ kg m −3 [ Zhu et al ., ], while the current is southward in winter and northward in summer in the Karimata Strait [e.g., Susanto et al ., ]. The seasonal reversal of surface current does not construct a steady state of circulation, and more importantly, it has been extensively analyzed and attributed mainly to the wind stress curl by previous studies [e.g., Qu , ; Gan et al ., ; Gan and Qu , ; Gan et al ., ].…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Black and purple stars are sampling locations of this article and Schröder et al (), respectively. The surface and intermediate currents are basically depicted by Zhu et al () and Hu et al (): The surface currents are indicated by light blue arrows (winter) and yellow arrows (summer); the intermediate currents are indicated by dark blue arrows (winter) and orange arrows (summer). The Kuroshio Current is indicated by the black arrows (Fang et al, ).…”
Section: Regional Backgroundmentioning
confidence: 99%